Effectiveness of Corn Cob Activated Carbon In Removing Total Suspended Solids And Total Chromium In Batik Waste - Canda Diwratna Wulandari; Anis Artiyani; Maria Roslyn Dwiputri; Hery Setyobudisudarso (International Journal of Science and Environment (IJSE), 2026)
The batik production process involves several stages that generate liquid, gaseous, and solid waste. Furthermore, the process requires significant amounts of water. Without proper treatment, this can degrade water quality. Certain waste parameters, specifically Total Suspended Solids (TSS) and Total Chromium, exceed established quality standards. Given the limitations batik artisans face regarding infrastructure, resources, and access to technology, there is a need for a waste treatment model that is simple, modular, and easy to maintain. Adsorption is a widely used method for wastewater treatment, with corn cobs serving as an adsorbent. The purpose of this study is to test the ability of activated carbon from corn cobs to reduce TSS and total chromium in batik wastewater. The adsorbent dosage was 1.5 grams and 3 grams, with stirring times of 30, 60, and 90 minutes, at a stirring speed of 200 rpm. The results indicate that activated carbon derived from corn cobs effectively adsorbed TSS and Total Chromium from batik wastewater. The highest effectiveness of the percentage of TSS and Chromium content allowance at the variation of activated carbon dose of 3 grams and at the contact time of 90 minutes with the percentage of TSS elimination of 80% and Total Chromium of 97%, but it has not met the quality standards in accordance with the Ministry of Environment and Foresty Regulation No. 16 of 2019, namely TSS of 50 mg/L and total Chromium of 1 mg/L.